Republic of Palau : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
This 2014 Article IV Consultation highlights that after two years of strong expansion, growth is estimated at about zero percent in the fiscal year 2013 (FY2013, ending in September) in the Republic of Palau owing to declines in construction and tourism. Inflation moderated to 2 3/4 percent (annual average) in FY2013 thanks to stable international food and fuel prices, and it is expected to stay at about 3 percent in FY2014. Growth is projected to increase to 1 3/4 percent in FY2014 and to 2u-2 1\2 percent over the medium term driven by the recovery in tourism and infrastructure developments.